Curcumin Effectivity on Hepar and Reproductive Organ Recovery Male Mice (Mus musculus L) after Methoxychlor Exposure - Mahriani Mahriani; Susantin Fajariyah; Eva Tyas Utami (Biota, 2020)
Methoxychlor (MXC) is an insecticide (DDT derivates) that has the potential for bioaccumulation in mammal and causes a disruptive effect on the hepar and reproductive system. This study was done to find out the benefits of curcumin as a natural ingredient to overcome the negative impact of Methoxychlor (MXC) on hepar and male reproductive organ of Balb’C mice (Mus musculus L). The study was carried out in a Completely Randomized Design (CRD) Posttest Only Control Group Design used four treatments and six replications. The curcumin treatment after administration of MXC was carried out by gavage with curcumin doses: 0.05; 0,1; and 0.2 mg/g body weight, every day for two weeks, respectively. Histological observations of the liver, and testis was performed using the paraffin method and Hematoxylin Eosin stained. The results showed that MXC exposure caused liver disruption by increasing the number of pycnotic necrotic hepatocytes and hydrophic degeneration hepatocytes. On the male reproductive organ, MXC caused testis impairment by reducing the number of Sertoli cells and Leydig cells, spermatogenic cell counts, and the diameter of seminiferous tubules. The administration of curcumin at doses of 0.1 mg/g bw in mice exposed to methoxychlor can reduce the number of hydrophic degeneration hepatocytes and tend to reduce the number of pycnotic hepatocytes; and also increase the number of Sertoli cells, the number of spermatogenic cells, and the diameter of the seminiferous tubules, and tend to reduce the amount of Leydig cells. Curcumin treatment tends to recover hepar dan testis disruption of mice that were exposed by MXC.